COMMUNICATIVE STRATEGIES AND COGNITIVE MECHANISMS IN CHINESE GOODS ADVERTISING TEXTS IN RUSSIA Ding Hao (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-35-42The main task of marketers when advertising Chinese goods in Russia is related to the right choice of tactics and communicative and cognitive techniques that allow us to talk about the success of advertising within a particular national market. The study identified the main communication strategies and tactics, as well as cognitive mechanisms that determine the effectiveness of advertising.Key words: communication strategies, cognitive mechanisms, advertising of Chinese goods, advertising discourse, advertising text, communication tactics